Perceptions of climate change and climate change policies within the tourism sector in Mauritius : a thesis prepared in partial fulfilment of the requirements for the degree of Master of Environmental Management at Massey University, New Zealand - Dhoomun, Lovisha (Massey University, 2016)
Tourism in small island developing states (SIDS) is particularly vulnerable to climate change. The phenomenon is predicted to reduce the demand for Tourism in SIDS as temperatures at these destinations become uncomfortably Hot and temperate destinations close to tourists’ countries of origin become More appealing. Climate change is also expected to have significant economic Implications for the tourism industry in island nations due to sea level rise, Storm surges and more intense cyclones which can damage coastal Infrastructure, disrupt tourism operations, contribute to environmental Degradation and create a less attractive image of the destination. These Impacts may be reduced through a planned adaptation approach which is guided by national policies and mediated by authorities. However, the complex and uncertain nature of climate change requires more than only expert opinions to ensure that implemented policies are effective. Tourism is the most important export-oriented economic activity in Mauritius. However, rapid tourism development has led to environmental degradation in coastal areas. Climate change is predicted to exacerbate these conditions and further deteriorate the environmental attributes on which tourism depends. This research examines the climate change risk perceptions among stakeholders within the tourism sector in Mauritius. It also explores their perceptions of the public policies which guide the management of climate change impacts, their policy preferences and the factors which they view as barriers to an effective approach to climate change. A conceptual framework based on the literature on risk perceptions was developed to guide this research and a mixed method approach comprising a self-administered survey and semistructured interviews was adopted for data collection. Information was gathered regarding stakeholders’ level of concern about climate change, their past experience of climate change impacts, sources of information, levels of trust in institutional responses, and their preferred approach to managing climate change impacts. Results revealed that climate change is perceived as representing significant risks for Mauritius, both for the participants on a personal level and for the tourism industry. Climate change is viewed as a phenomenon which leads to unpredictable and potentially fatal consequences, and therefore, as having high catastrophic potential. Past experience and a lack of confidence in government institutions’ capacity to successfully manage the impacts strongly influenced these perceptions. Stakeholders’ preferred policy options included education, raising awareness, stricter regulations for environmental conservation and mitigation of greenhouse emissions. The majority of participants demonstrated a lack of awareness of the importance of adaptation in Mauritius, and therefore viewed the current institutional approach, which appropriately focuses on adaptation, as being inadequate or insufficient. It is recommended that communication among tourism stakeholders is strengthened and information about adaptation is disseminated to stakeholders through sources perceived as being credible. Keywords: climate change, tourism, risk perceptions, policy, Small Island Developing States, Mauritius.
Keywords: Tourism; Climatic changes; Climate change; Government policy; Risk perception; Small Island Developing States; Mauritius; Research Subject Categories::SOCIAL SCIENCES::Business and economics